EXPLORING FEEDBACK MECHANISMS TO STRENGTHEN ESL LEARNER ENGAGEMENT AND OUTCOMES - Ibrahim, Rahayu Irdiana; Abdullah, Fadhilahanim Aryani; Lateh, Nor Hazwani Munirah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2026)
This study examines how the deliberate use of structured feedback, alongside continuous teacher reflection, contributes to improved learner engagement and academic achievement in English as a Second Language (ESL) settings. Informed by formative assessment frameworks and reflective pedagogy, the research adopted a mixed-methods approach in the Kota Bharu District. Data were collected through a combination of student questionnaires, achievement records, semi-structured teacher interviews, reflective teaching logs, and systematic classroom observations. The results indicate a positive shift in students’ learning behaviours, including increased motivation, active participation, and enhanced language development. Insights from qualitative findings highlight the importance of feedback that is purposeful and responsive, as well as reflective practices reinforced through collaborative professional learning. While practical constraints such as class size and instructional time posed challenges, engagement in Professional Learning Communities (PLCs) supported ongoing pedagogical improvement. The study underscores the value of integrating feedback and reflection as complementary strategies for strengthening instructional quality and learner outcomes, offering relevant considerations for ESL practitioners and education stakeholders.